Dampak Pembelajaran Daring terhadap Motivasi Belajar Mahasiswa di Era Digital dengan Pendekatan Technology Acceptance Model - Ajeng Triandari; Muhammad Irwan Padli Nasution (Lembag, 2025)
The rapid advancement of digital technology has encouraged higher education institutions to adopt online learning more extensively and systematically. This shift has not only transformed academic interaction patterns but also has the potential to influence students’ learning motivation. This study aims to analyze the effect of online learning on students’ learning motivation using the Technology Acceptance Model (TAM). The model is employed to measure how perceived ease of use and perceived usefulness shape students’ acceptance of learning technologies, and how this acceptance subsequently impacts their motivation to learn.Data were collected through questionnaires distributed to students participating in online learning, and the responses were analyzed to examine the relationships among perception, technology acceptance, and learning motivation. The results indicate that positive perceptions of the ease of use and usefulness of online learning platforms significantly contribute to increased learning motivation. The more students perceive online learning technologies as accessible and beneficial, the higher their engagement and intrinsic motivation in the learning process.These findings offer important implications for educational institutions in designing, evaluating, and developing effective and user-centered online learning systems. Optimizing learning technologies can serve as a key strategy to enhance the overall quality of learning as well as students’ motivation in higher education settings.